ЯПОНЫ УЛС ТӨРИЙН ДЭГЛЭМ - Ж.ТӨРТОГТОХ,; Э.Саранцэцэг, (Politology, 2023)
Politics of Japan is conducted in a framework of a parliamentary representative democratic monarchy where the Prime Minister of Japan is the head of government and the head of the Cabinet that directs the executive branch. Legislative power is vested in the Diet, which consists of the House of Representatives and the House of Councillors. Japanese politics uses a multi-party system. The judicial power is vested in the Supreme Court and lower courts. In academic studies, Japan is generally considered a constitutional monarchy with a system of civil law. Japan is a country of earliest history of democracy among Asian nations, and has its own unique culture and history. Japan adjusted the democracy as a form of government to its unique culture and people's mindset when adopting democracy, not directly applied it. It is not capitalist principle of survival of the fittest, rather it was a philosophy of equality among citizens that prevailed in the society.